The role of microcredit schemes to alleviate poverty: an in depth analysis of urban poor entrepreneurs in Kuala Lumpur, Malaysia - Abdul Manaf, Halimah (2016)
Previous literature on microcredit schemes tend to focus on the benefits of these scheme on rural poor.This study, meanwhile, tries to explore the potential advantages of microcredits schemes on the urban poor.There is currently limited literature that document how urban poor have benefited from microcredit schemes especially in regard to providing additional income to support their families.The fact that poor residents in urban areas are not able to access bank loans to start their business forces them to borrow money from loan sharks.This situation puts the aspiring poor urban entrepreneurs at an even disadvantage position when they could not pay back the loan. Building upon this framework, this study surveys 257 poor urban entrepreneurs from Kuala Lumpur, a capital city of Malaysia. The overall finding reveals a positive and significant correlation between receiving microcredit schemes and business sustainability.Specifically, respondents highlight that their income has increased between 10-50% through microcredit scheme assistance. This finding highlights the importance of microcredit schemes as part of government strategy to reduce urban poverty.